REGIONAL CHILDREN'S CENTER OF RATIONAL NUTRITION - NEW FORM OF INFANT NUTRITION OPTIMIZATION - O.V. Yavorskaya; I.A. Tishevskoy; I.A. Ogoshkova ("Paediatrician" Publishers LLC, 2006)
The article highlights the first results of the work of the new organization form of infant feeding optimization - regional children's center of sensible nutrition in Chelyabinsk region. It provides for combination of medical and psychohygienic work to support breast feeding and prevent eating disorders.Key words: breast feeding support, prevention of alimentary conditioned diseases, infants.